The Construction of Minimal (b,t)-Blocking Sets Containing Conics in PG(2,5) with the Complete Arcs and Projective Codes Related with Them - Al-Mukhtar, Amal Shihab; Thumai, Hani Sabbar (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A (b,t)-blocking set B in PG(2,q) is set of b points such that every line of PG(2,q) intersects B in at least t points and there is a line intersecting B in exactly t points. In this paper we construct a minimal (b,t)-blocking sets, t = 1,2,3,4,5 in PG(2,5) by using conics to obtain complete arcs and projective codes related with them.